Into the wild: uncertain frontiers and sustainable human–nature interactions - Patterson, Jennifer (Frontiers in Sociology, 2024)
Humans seldom consider themselves as animals, and that humans are animals is a truth frequently turned into an insulting metaphor indicating “uncivilized” behavior in many cultures. Interestingly, the “civilizing” aspects of Western Culture in the Global North are historically derived from traditions of democracy based on living in cities from which the wild has been banished. This is embedded in the English language since civilizing and civilization come from the Latin for city, civitas, the place where citizens hold voting rights. Beyond the gates of civilization is the wild. How the wild and nature have been constructed and demarcated is an enormously complex and enduring challenge in western philosophy as it relates to knowledge-making, existence, truth, and reality. Indeed, whilst people generally believe they know what nature means, they rarely realize that little in nature is wild. Furthermore, the concept of uncertainty, central to the pandemic, is compounded by climate instability and a potentially disastrous future. This is breaking down what is known, requiring porous and flexible conceptual frontiers and a transdisciplinary approach. This article traces the linguistic separation of humans from their animal origins and wilder environments for political and increasingly greedy economic purposes. It explores the acknowledged complexity of healthy human–nature interactions, juxtaposing information mainly from the humanities and social sciences. Demonstrating how unhealthy the current paradigm has proven to be for humans and the natural world, it brings together conflicting information to disrupt traditional certainties using an innovative bricolage methodology. It weaves and combines different ways of knowing as it considers forms of knowledge-making, rewilding, foraging, the place of magical thinking, and vital force. It concludes that a new paradigm is needed to enable a way of working toward any vision of healthy human–nature interaction.